Neurofibromatosis type 1 associated to peripheral nerve sheath and colon malignant tumor - Valle, Rubén (2009)
Neurofibromatosis type 1 is a dominant autosomal disease caused by mutation of the neurofibrin gene located in chromosome 17q11.2. This disease presents a variety of clinical manifestations and predisposition to develop tumors, leading to high mortality. We report the case of a patient with neurofibromatosis type 1 diagnosis who developed a malignant tumor of peripheral nerve sheath and colon cancer. The authors review the literature as well as the clinical factors, imaging and histological features associated to neurofibromas malignant transformation.